Genetic analysis in ivygourd (COccinia grandis (L) viogt) - Siby Varghese (Department of Plant Breeding and Genetics, College of Agriculture, 2003)
The present investigation entitled "Genetic Analysis in Ivygourd (Coccinia grandis (L) Voigt.) was conducted at the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani during 1999-2001. Objective of the study was to estimate the genetic basis of different characters, genetic divergence in the germplasm and to formulate a selection index for identifying superior types. The material for the experiment was 90 different local cultivars collected from different agroclimatic regions. The data for the investigation were collected from two field experiments, each laid out in Randornised Block Design with three replications. In Experiment I a collection of 50 genotypes of ivygourd was grouped into 11 clusters using Mahalanobis D2 statistic and based on eight morphological characters. Five genotypes Kuriyabandar local I, Kuriyabandar local Ill, Pilangatta local 11 & III and Kudlu local I, could not be grouped with others and so are kept as independent clusters. The cluster C IX was found to have maximum intercluster distance with seven of the eleven clusters formed. This was followed by C 11 which showed maximum divergence with four out of the eleven clusters. The results suggest that selection of parents from these divergent clusters will be effective in future hybridisation programme. The three superior crosses identified were Balthangadi local I x Pilangatta local 11, Bandargrarn local I x Pilangatta local 11 and Seetharnbeta local I x Pilangatta local II. Number of flowers per plant and number of leaves per plant were found to be the two characters that contributed